Cutting Tools

JP7643106B2Active Publication Date: 2025-03-11MITSUBISHI MATERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021043171
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-03-11
Estimated Expiration
2041-03-17

AI Technical Summary

Benefits of technology

【0012】 本発明の切削工具は、耐塑性変形性と耐チッピング性に優れ、チタン合金やステンレス鋼等の難削材の切削加工に供しても優れた耐久性を発揮する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643106000011
    Figure 0007643106000011
  • Figure 0007643106000012
    Figure 0007643106000012
  • Figure 0007643106000013
    Figure 0007643106000013
Patent Text Reader

Abstract

To provide a cutting tool excellent in durability since a blade edge has plastic deformation resistance, and chipping resistance even if using for cutting work of a hard-to-cut material such as titanium alloy and stainless steel.SOLUTION: A cutting tool is composed of a material having a composition containing 4.0-15.0 mass% of any one or two of Co and Ni, 0.5 mass% or less of Cr3C2, 0.5 mass% or less of VC, 12.0 mass% or less of one, or two or more of any of TaC, NbC, TiC, ZrC, and HfC, and a balance of WC and inevitable impurities, where the average particle diameter of WC is 0.5-4.0 μm, and the percentage of a measured point having a KAM value in a bonded phase of one or less is 70% or more in a surface region to the inside departing from the surface by 10 μm, and 60% or less in an inside region departing from the surface by 15-25 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cutting tool using a cemented carbide (WC-based sintered alloy). [Background technology]

[0002] Cemented carbide is used as a cutting tool for metals because of its excellent mechanical strength, thermal fatigue resistance, etc. However, the conditions of use of these cutting tools are becoming more severe due to the increasing efficiency of cutting processes, and cutting tools are required to have even greater durability.

[0003] For this reason, various proposals have been made to improve the durability of cemented carbide used in cutting tools, including those that control the crystal grain size of the binder phase in order to improve hardness, toughness, and breakage resistance.

[0004] For example, Patent Document 1 describes a cemented carbide in which the crystal structure of Co satisfies 0≦I(Co·hcp) / I(Co·fcc)≦0.1 (I(Co·hcp) is the X-ray diffraction intensity on the (101) plane of Co with an hcp structure, and I(Co·fcc) is the X-ray diffraction intensity on the (111) plane of Co with an fcc structure) and further the lattice constant of Co is 3.570 or more, and the cemented carbide is said to have both toughness and strength, in particular impact strength.

[0005] Furthermore, for example, Patent Document 2 describes a cemented carbide including a hard phase made of at least one selected from WC, TiC, TiN, and TiCN, and a binder phase made of an iron-group metal, the binder phase being formed by electric current pressure sintering using binder phase powder having an average particle size three times or more that of the hard phase powder, the binder phase having a flat shape with an aspect ratio of 5 to 20 in a cross section of the hard alloy parallel to the pressure axis of a sintering device performing electric current pressure sintering, and a binder phase structure having a directional arrangement extending in a direction perpendicular to the pressure axis, and the cemented carbide is said to have high toughness and excellent hardness and strength.

[0006] Furthermore, for example, Patent Document 3 describes a fine-grained cemented carbide having an average WC grain size of 0.8 μm or less and an average binder phase grain size of 200 μm or less, and the cemented carbide is said to have excellent breakage resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4537501 [Patent Document 2] Patent No. 4177467 [Patent Document 3] JP 2004-346370 A Summary of the Invention [Problem to be solved by the invention]

[0008] According to the inventors' investigations, it was found that when the cemented carbide alloys described in Patent Documents 1 to 3 are used as cutting tools for hard-to-cut materials such as titanium alloys and stainless steel, the plastic deformation resistance and chipping resistance are insufficient.

[0009] The present invention has been made in consideration of the above circumstances, and has an object to provide a cutting tool that has excellent durability and improves the plastic deformation resistance and chipping resistance of the cutting edge, even when used for cutting difficult-to-cut materials such as titanium alloys and stainless steel. [Means for solving the problem]

[0010] The present inventors have conducted extensive research in order to obtain a cutting tool that achieves the above-mentioned object, and have discovered that if the cemented carbide constituting the cutting tool has a predetermined composition and a region having a predetermined ratio of a binder phase composed of a plurality of crystals is present in the vicinity of the surface of the cutting tool, the cutting edge has resistance to plastic deformation and chipping, and is highly durable.

[0011] The present invention is based on this finding and is as follows. "(1) 4.0 to 15.0 mass% of either Co or Ni, Cr 3 C 2 0.5% by mass or less, VC less than 0.5% by mass, Contains 12.0 mass% or less of one or more of TaC, NbC, TiC, ZrC, and HfC, The balance is WC and unavoidable impurities, The average particle size of the WC is 0.5 to 4.0 μm, The ratio of measurement points in the bonding phase having a KAM value of less than 1 is 70% or more in a surface region from the surface to an interior region 10 μm away, and 60% or less in an interior region 15 to 25 μm away from the surface. A cutting tool characterized by: (2) The cutting tool according to (1) above, characterized in that the cutting edge has a surface coating layer." Effect of the Invention

[0012] The cutting tool of the present invention has excellent resistance to plastic deformation and chipping, and exhibits excellent durability even when used in cutting difficult-to-cut materials such as titanium alloys and stainless steel. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram showing the measurement area of ​​the KAM value. [Diagram 2] FIG. 1 is a schematic diagram illustrating a method for measuring a KAM value. [Diagram 3] 1 is a schematic diagram showing an example of the amount of plastic deformation on the flank of a cutting edge, in which the upper figure (the rake face) is a plan view and the lower figure (the flank on the cutting edge side) is a side view. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, a cutting tool according to an embodiment of the present invention will be described, particularly when used as an insert. In the specification and claims, when a numerical range is expressed using "M to N" (where M and N are both numerical values), the range is intended to include the upper limit (N) and lower limit (M) numerical values.

[0015] 1.Composition The composition of the cutting tool of this embodiment is: 4.0 to 15.0 mass% of either Co or Ni, Cr 3 C 2 0.5% by mass or less, VC less than 0.5% by mass, Contains 12.0 mass% or less of one or more of TaC, NbC, TiC, ZrC, and HfC, The balance consists of WC and unavoidable impurities. The following explains each in order.

[0016] (1) Co and Ni The content of either one or both of Co and Ni is preferably 4.0 to 15.0 mass %. The reason is that if it is less than 4.0 mass %, chipping resistance and fracture resistance are insufficient, while if it is 15.0 mass % or more, plastic deformation resistance and wear resistance are insufficient. Co and Ni are mainly present in the binder phase, and one or both of Co and Ni account for 50 mass % or more of the main components of the binder phase, that is, of all the components forming the binder phase.

[0017] The binder phase may contain one or more of Cr, Ta, Nb, Ti, Zr, Hf, and V. When these elements are present in the binder phase, they are presumed to be in a solid solution state in the binder phase. Furthermore, the binder phase may contain W and C, which are components of the hard phase, and other unavoidable impurities.

[0018] (2)Cr 3 C 2 In order to improve the plastic deformation resistance of the cutting tool, it is preferable to contain Cr (although the inclusion of Cr is not essential). The content of Cr in the entire cutting tool is as follows: 3 C2 In terms of mass, it is preferably 0.5 mass % or less.

[0019] (3) V.C. In order to improve the plastic deformation resistance of the cutting tool, it is preferable to contain V (although the inclusion of V is not essential). The content of V is preferably 0.5 mass % or less, calculated as VC, based on the entire cutting tool.

[0020] (4) TaC, NbC, TiC, ZrC and HfC One or more of TaC, NbC, TiC, ZrC and HfC form a γ phase. The γ phase does not have to exist, but if it does exist, it is preferable that the content of one or more of the compounds represented by MC is up to 12.0 mass% based on the entire cutting tool, assuming that the compound is a carbide in which M (metal atom) and C are bonded in a 1:1 ratio. The reason for this is that if the content exceeds 12.0 mass%, the wear resistance of the cutting tool becomes insufficient, and aggregates are easily formed inside the cutting tool, which become the starting point for chipping.

[0021] (5) WC WC is the main component of the hard phase. The hard phase may contain unavoidable impurities that are inevitably mixed in during the manufacturing process.

[0022] The average particle size of WC is preferably 0.5 to 4.0 μm. If it is less than 0.5 μm, the hard phases slip between each other, resulting in insufficient plastic deformation resistance and chipping resistance, whereas if it exceeds 4.0 μm, insufficient wear resistance cannot be obtained. The average particle size of WC is more preferably 1.0 to 3.0 μm.

[0023] The average grain size of WC was determined by observing at a pixel size, determining the area of ​​at least 4,000 hard phases by image analysis, and calculating the diameters of circles equal to the areas, and averaging them.

[0024] Specifically, for example, one field of view is 30 μm × 70 μm, pixel size is 40 nm × 40 nm, and when a region from the surface of the cutting tool (described later) to a depth of 30 μm is observed in cross section, the number of WC particles and the number of bonding phases in the region are each 4000 or more, and each observation field of view includes 60 to 70 μm of the cutting tool surface, and multiple fields of view (5 or more) are observed at a magnification of, for example, 1000 times.

[0025] (6) Inevitable impurities As described above, the hard phase and the binder phase may contain impurities that are inevitably mixed in during the manufacturing process, and the amount of impurities is preferably 0.3% by mass or less, with the total mass of the cutting tool being 100% by mass.

[0026] 2. Organization of the Binding Phase As shown diagrammatically in FIG. 1, it is preferable that the ratio of measurement points in the binder phase having a KAM value of less than 1 is 70% or more in the surface region (O) of the cutting tool extending from the surface of the cutting tool to the interior at a distance of 10 μm, and is less than 60% in the interior region (I) of the cutting tool extending from 15 to 25 μm from the surface. Here, the KAM value is also called the local orientation difference average value.

[0027] When the KAM value in the binder phase takes such values ​​in each region away from the surface of the cutting tool, the fracture resistance and plastic deformation resistance are improved.

[0028] Here, the KAM value is measured as follows.

[0029] (1) Definition of grain boundaries Using an electron beam backscattering analyzer, an observation field of view is set, for example, 100 μm wide and the vertical measurement area (area 10 μm away from the surface, 15 to 25 μm away from the surface) in a longitudinal section (described later), from the surface of the cutting tool toward the inside, and measurements are taken at 40 nm intervals. The observation field of view is 5 or more. In the observation field of view, the measurement points (pixels) are present discretely, but the area up to the middle between adjacent measurement points (a regular hexagon can be exemplified) is represented by the measurement result of the measurement point. When there is an orientation difference of 5 degrees or more between adjacent measurement points among these measurement points, the area up to the middle is defined as a grain boundary.

[0030] However, a measurement point that has an orientation difference of 5 degrees or more from all of its adjacent measurement points, or that exists alone with no adjacent measurement points, is not treated as a crystal grain, and a measurement point consisting of two or more connected measurement points is treated as a measurement point.

[0031] (2) Measurement of KAM value Then, the average value of the misorientation between two adjacent pixels in a crystal grain is calculated and defined as the KAM (Kernel Average Misorientation) value. Generally, when expressing the KAM value at pixel i in a mathematical formula, if the measurement area is divided into regular hexagons and analyzed, it can be expressed as the average of the misorientation between up to six measurement points surrounding the point of interest (measurement point of interest, pixel) by the following formula 1. Note that in [Formula 1], m is the number of pixels adjacent to measurement point i within the same crystal grain, α k、i represents the orientation difference between pixel i and adjacent pixel k. In other words, when the KAM value at the attention point U shown in Figure 2 is expressed mathematically, since there are six pixels to be measured, 1 to 6, it can be calculated by the following [Equation 2], and the KAM value at the attention point V, since there are two pixels to be measured, 1 and 2, it can be calculated by the following [Equation 3].

[0032]

number

[0033]

number

[0034]

number

[0035] In the claims and the specification, the surface of a cutting tool refers to a line connecting the deepest valley and the second deepest valley on the cutting tool surface in a longitudinal section when observed at a magnification of 100 to 200 times and a visual field of 500 to 1000 μm horizontal x 400 to 800 μm vertical. For example, 10 μm away from the surface of a cutting tool refers to 10 μm away from the surface of the cutting tool on a perpendicular line to this line toward the inside of the tool.

[0036] The longitudinal section refers to a section perpendicular to the surface of the cutting tool when the cutting tool is an insert and the surface of the cutting tool is treated as a horizontal plane, ignoring any unevenness on the surface, and this perpendicular direction does not necessarily coincide with the direction of the perpendicular line described above. Also, when the cutting tool has a central axis such as a drill, the longitudinal section refers to a section perpendicular to this axis.

[0037] 3.Surface coating layer The cutting tool of the present embodiment can achieve the above-mentioned object as it is, but a surface coating layer may be provided on the surface of the cutting tool including the cutting edge. By providing a surface coating layer, the above-mentioned object can be achieved more reliably. There are no particular restrictions on the surface coating layer, and any known surface coating layer can be used as appropriate. EXAMPLES

[0038] Next, the present invention will be specifically described with reference to examples, but the present invention is not limited to these examples.

[0039] 1. Mix with raw powder First, as powders for sintering, WC powder with an average particle size (d50) of 0.5 to 4.0 μm, and Co powder, Ni powder, and Cr powder, all of which have an average particle size (d50) in the range of 1.0 to 4.0 μm, as shown in Table 1, were used. 3 C 2Powder, TaC powder, NbC powder, TiC powder, ZrC powder, HfC powder, and VC powder were prepared.

[0040] 2. Preparation of the molded body Next, these powders were mixed to obtain the composition shown in Table 1 to prepare powder for sintering. The powder was wet mixed in a ball mill for 72 hours, dried using a spray dryer, and then pressed at a pressure of 100 MPa to obtain the shape of ANSI designation CNMG432MS to produce a powder compact.

[0041] 3. Sintering Next, the powder compacts were subjected to a main sintering step in which they were held at a predetermined temperature for a predetermined time. In this example, the conditions shown in Table 2 were used, that is, the compacts were heated to a holding temperature range of 1350 to 1450°C in a vacuum atmosphere of 0.1 Pa or less, and held at the holding temperature for 60 to 120 minutes.

[0042] 4. First blasting treatment (dry blasting treatment) Cemented carbide granulated powder (the same granulated powder as that used in producing the cemented carbide) was used as the abrasive grains, and processing was performed under the conditions shown in Table 2. The conditions shown in Table 2 were roughly as follows. Grain size: diameter 100~200μm Blasting pressure: 0.35~0.40MPa Projection time: 15~20 seconds Projection angle: 35~55 degrees to the normal of the cutting tool surface The normal line to the cutting tool surface refers to the normal line to the cutting tool surface when the cutting tool surface is treated as a horizontal plane, ignoring any irregularities on the cutting tool surface, and does not necessarily coincide with the perpendicular line described above.

[0043] 5.Heat treatment As shown in Table 2, the sample was held in a vacuum atmosphere of 0.1 Pa or less at 700 to 1000° C. for 5 to 50 hours.

[0044] 6. Second blasting treatment (wet blasting treatment) As a blasting treatment liquid, Al 2 O 3The treatment was carried out using water containing abrasive grains under the conditions shown in Table 2. The conditions shown in Table 2 were roughly as follows: Media (abrasive) size: 170~500 (mesh) Media concentration: 15-60% by mass Blasting pressure: 0.10~0.15MPa Projection time: 6~60 seconds Projection angle: 35~55 degrees to the normal of the cutting tool surface The normal line to the cutting tool surface refers to the normal line to the cutting tool surface when the cutting tool surface is treated as a horizontal plane, ignoring any irregularities on the cutting tool surface, and does not necessarily coincide with the perpendicular line described above.

[0045] The above steps 4 to 6 were each repeated twice.

[0046] 7. Post-processing Next, machining and grinding were performed to shape the CNMG432MS, and cutting tools 1 to 10 shown in Table 3 (hereinafter referred to as Examples 1 to 10) were produced.

[0047] For comparison, cutting tools 1' to 7' of comparative examples (hereinafter referred to as Comparative Examples 1' to 7') were manufactured. The manufacturing process is one in which the first blasting process, heat treatment process, and second blasting process are omitted from the manufacturing processes of Examples 1 to 10 (in Table 2, each process condition is marked with "-"), or one in which the first blasting process or heat treatment process shown in Table 2 was performed outside the manufacturing conditions described above.

[0048] That is, the powder for sintering, which is blended according to the blending composition shown in Table 1, is wet mixed in a ball mill for 72 hours, dried by a spray dryer, and then pressed under a pressure of 100 MPa to produce a green compact having the shape of CNMG432MS. The green compact is then sintered under the conditions shown in Table 2, namely, a heating temperature of 1350°C to 1450°C, a heating holding time of 60 to 120 minutes, and a vacuum atmosphere of 0.1 Pa or less. The first blasting treatment is performed under the conditions of a blasting pressure of 0.10 to 0.20 MPa, a projection time of 15 to 20 seconds, and a projection angle of 35 to 55 degrees relative to the normal line of the tool surface. The heat treatment step is performed under the conditions of a heating temperature of 400 to 850°C, a heating holding time of 10 to 50 hours, and a vacuum atmosphere of 0.1 Pa or less. The second blasting treatment is performed under the conditions of a media (abrasive grains): Al 2 O 3 The blasting conditions were as follows: abrasive grain, media size: 230-500 (mesh), blast pressure: 0.10-0.15 MPa, projection time: 6-60 seconds, projection angle: 35-55 degrees relative to the normal to the tool surface. These were then machined and ground to produce comparative example tools 1'-7' shown in Table 4, which have a CNMG432MS insert shape.

[0049] For the cutting tools of Examples 1 to 10 and Comparative Examples 1' to 7', the component composition and average grain size of WC were determined based on the above-mentioned observation fields, and the results are shown in Tables 3 and 4. It was confirmed that the content ratio of unavoidable impurities was within the above-mentioned preferable range.

[0050] [Table 1]

[0051] [Table 2]

[0052] [Table 3]

[0053] [Table 4]

[0054] Next, a hard coating layer having an average thickness shown in Table 5 was formed on the surface of each of the above-mentioned Examples 1 to 10 and Comparative Examples 1' to 7' by a CVD method.

[0055] [Table 5]

[0056] The following cutting tests were carried out on Examples 1 to 10 and Comparative Examples 1' to 7' to measure the amount of plastic deformation on the flank of the cutting edge and observe the state of wear of the cutting edge.

[0057] In the following cutting tests, the following was adopted as the amount of plastic deformation on the flank of the cutting edge: The amount of plastic deformation on the flank of the cutting edge was determined by the amount of deformation of the ridge of the cutting edge caused by the cutting, based on the undeformed ridge of the cutting edge before cutting.

[0058] Specifically, as shown in Fig. 3, for the flank (12) on the main cutting edge side of the tool, a line segment was drawn on the ridge where the flank (12) on the cutting edge (13) side and the rake face (11) intersect at a position sufficiently away from the cutting edge, and the line segment was extended in the direction of the cutting edge portion, and the distance between the extended line segment (15) and the ridgeline of the cutting edge portion (perpendicular to the extended line segment) was measured at the furthest point, and this was defined as the amount of plastic deformation (14) on the flank of the cutting edge. In addition, the wear state of the cutting edge was observed after the cutting time was completed. Table 6 shows the results of the cutting tests.

[0059] Wet external diameter turning of Ti-6Al-4V alloy round bar (diameter 200 mm) Work material: Ti-6Al-4V alloy Cutting speed: 70m / min Cutting depth: 1.0mm Feed: 0.16mm / rev Cutting time: 5 minutes

[0060] [Table 6]

[0061] Moreover, the following cutting test was carried out on the above-mentioned Inventions 1 to 4 and Comparative Examples 1' to 4' not having the above-mentioned coating layer, and the amount of plastic deformation on the flank of the cutting edge was measured, and the state of wear of the cutting edge was observed. Table 7 shows the results of the cutting tests.

[0062] Wet external diameter turning of JIS SUS304 round bar (diameter 200 mm) Work material: JIS / SUS304 Cutting speed: 50m / min, Cutting depth: 1.0mm, Feed: 0.11mm / rev, Cutting time: 5 minutes, Uses wet water-soluble cutting oil.

[0063] [Table 7]

[0064] According to the test results shown in Tables 6 and 7, all of the Examples exhibit excellent resistance to plastic deformation without causing severe chipping that would affect the tool life. In contrast, the Comparative Examples showed large plastic deformation of the tool at a given cutting time, and some samples showed chipping at the cutting edge. That is, the Examples have high resistance to plastic deformation and chipping because the proportion of measurement points in the binder phase with a KAM value of less than 1 is 70% or more in the surface region up to 10 μm away from the surface and 70% or less in the inner region 15 to 25 μm away from the surface. [Explanation of symbols]

[0065] 1~6 Grain number 11. Scooping surface 12 Cutting edge side flank 13 Cutting edge 14. Composite deformation on flank 15 Line segment extending from the ridge where the flank and rake faces intersect O Surface area of ​​the cutting tool I. Inner area of ​​cutting tool B grain boundary P Measurement point (pixel) U Points to note V Points of note

Claims

1. One or both of Co and Ni are 4.0 to 15.0 mass%; Cr 3 C 2 0.5 mass % or less, VC at 0.5% by mass or less, Contains 12.0 mass% or less of any one or more of TaC, NbC, TiC, ZrC and HfC; The balance is WC and unavoidable impurities; The average grain size of the WC is 0.5 to 4.0 μm, The ratio of measurement points in the bonding phase having a KAM value of less than 1 is 70% or more in a surface region from the surface to an interior region 10 μm away, and 60% or less in an interior region 15 to 25 μm away from the surface. A cutting tool characterized by:

2. 2. The cutting tool according to claim 1, further comprising a surface coating layer on the cutting edge.

Citation Information

Patent Citations

  • Cemented carbide

    JP2004346370A

  • Coated cutting tools

    JP2015508716A

  • Surface-coated cutting tool having excellent defect resistance

    JP2019063899A

  • Coated cutting tool

    JP2019107720A

  • High toughness hard alloy and its manufacturing method

    JP4177467B2